EVALUASI SIFAT KIMIA TANAH DAN HASIL KEDELAI PADA SISTEM AGROFORESTRI BERBASIS POHON JATI - Deni Prasetiyo; Djoko Purnomo; Supriyadi Supriyadi (Caraka Tani: Journal of Sustainable Agriculture, 2015)
Soybean is one of the most important food commodities in Indonesia and also it has high value. The needs continue to increase each year, but not offset by increased production become an issue that must be addressed. One attempt to increase soybean production is through the cultivation in agroforestry systems through improving the quality of soil fertility. This research aims to study the effect of various doses of litter teak and NPK fertilizer on chemical soil fertility and the potential of soybeans yield in agroforestry systems based teak crops. Experiments using a Randomized Complete Block Design (RCBD) with two factors, namely litter teak doses (0 ton ha-1, 2.500 ton ha-1, 5.000 ton ha-1, 7.500 ton ha-1) and doses of NPK fertilizer (60-60-60 and 60-120-60) on Grobogan soybean varieties. The variables measured were pH, organic matter content, N-total soil, cation exchange capacity (CEC), plant tissue of N, P-total soil, and component production. Data analysis using analysis of variance F-test based on the level of 5% and significantly different variables followed by Tukey’s method level of 5%. The results showed that combination treatment with various doses of teak litter NPK fertilizers can increase total nitrogen content of the soil with the highest yield of 1.69% on S1D2 treatment, but to organic matter, CEC, pH, and total soil P not significant effect. Component of soybean varieties of the highest Grobogan of 0.83 tons ha-1 in the treatment S1D1. The result was still below the average of the national soybean production.